Maximum Oxygen Volume Level (VO2MAX) of Female Volleyball Extracurricular Members - Hakim, Hikmad; Amahoru, Nurul Musifra (Sains Global Institut, Indonesia, 2024)
This study aimed to analyze the maximum oxygen volume level (VO2max) of female volleyball extracurricular members at State Vocational School 6 Makassar. A total of 30 participants aged between 15 and 18 years were selected using purposive sampling. The VO2max was measured using the multistage shuttle run test (Beep Test), complemented by anthropometric data collection including height and weight. The results showed that the average VO2max was 38.5 ± 4.2 ml/kg/min, indicating moderate cardiorespiratory fitness among the participants. Based on VO2max classification, 65% of the athletes were categorized as moderate, 20% as low, and 15% as high fitness levels. A significant positive correlation (r = 0.62, p < 0.01) was found between VO2max and weekly training frequency, suggesting that frequent training sessions improve aerobic capacity. However, no significant correlation was observed between VO2max and age or training duration (p > 0.05). These findings emphasize the importance of regular and consistent training to enhance aerobic fitness in adolescent female volleyball players. The study recommends the integration of aerobic conditioning programs into extracurricular training to further optimize performance. This research provides valuable baseline data for coaches and sports educators to develop effective training regimens tailored to young female volleyball athletes in vocational schools.